Evaluation of New Zoysiagrass Experimental Lines for Winter Hardiness and Turf Quality in the Transition Zone - R. Braun; J. Fry; M. Kennelly (Kansas Agricultural Experiment Station Research Reports, 2015)
A total of 881 zoysiagrass progeny originating from parental crosses at Texas A&M AgriLife Research – Dallas were planted in 2012, and an additional 104 progeny were planted by Kansas State University researchers in 2013. Starting in 2013, grasses were rated visually on 10 occasions through 2014. These ratings occurred throughout the year to evaluate winter survival and six turf quality characteristics to identify those progeny best adapted to the Kansas site. In September 2014, the top 20 of the original 985 progeny were selected and returned to Texas A&M AgriLife Research, Dallas, Texas, for propagation.
Keywords: turfgrass; zoysia; winter hardy; ' Meyer' zoysiagrass; Rhizoctonia large patch; Rhizoctonia solani Kuhn